"The End of the Story?": Introduction. (November 2014) - Grudzińska-Gross, Irena
Introduction to the selection of the papers presented at a two-day workshop "The End of the Story?" Problems and Perspectives of East European Literary Studies, " held at Princeton University on 8–9 February 2013.